Siegfried Kracauer, On friendship, editorial Las forty, Buenos Aires, 2019, 88 pages - Chausovsky, Alexis Ariel (2021)
The last decade has given the Spanish-speaking public the opportunity to become acquainted with the work of the German critic Siegfried Kracauer (1889-1966). Little by little, his texts have gained in strength and the body of his work, still scattered in Spanish, is gaining ground in contemporary scientific and philosophical production. The light that is now being shed on Kracauer's thought is beginning to displace him from the place assigned to him until a few years ago, where he was known mainly as a pioneer in film theory, although somewhat naively overcome.